PENGARUH STRATEGI BISNIS TERHADAP INTERNET FINANCIAL REPORTING DAN AGENCY COST SEBAGAI VARIABEL INTERVENING - M. Riduan Abdillah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, This reasearch aims to find empirical evidence about business strategies that directly influence the Internet Financial Reporting (IFR) and business strategies indirectly affect the Internet Financial Reporting (IFR) through agency cost as an intervening variable. The population of this research is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017. The sample of this research was taken by using purposive sampling method. The variable of this research consists of independent variables, namely the business strategy measured by the asset utilization efficiency (Warsini and Rossieta, 2013). The dependent variable, the Internet Financial Reporting (IFR), is measured by the Internet Disclosure Index (IDI) (Spanos and Mylonakis, 2006; Puspitaningrum and Atmini, 2012). Intervening variables, namely agency cost, are measured by ratio of operating expense divided by total sales per year (Ang, et al. 2000, Khan, et al. 2016). Control variables namely company size are measured by the natural logarithm of the company's total assets (Puspitaningrum and Atmini, 2012; Siagian, et al.2013). The results of this research find evidence that business strategies influence the Internet Financial Reporting (IFR) and Agency Cost mediate the influence of business strategies on Internet Financial Reporting (IFR).